Are infection control measures helpful in reducing paediatric ward infections?. Issue 6 (June 2018) - Beuvink, Yvonne; Hackett, Scott
Abstract: As the majority of children on paediatric wards, especially in winter, have infections all paediatricians will be involved in infection control and prevention (ICP) without realising it. ICP measures include decisions on isolation of patients, which can be difficult with small numbers of cubicles. Children, who are highly infectious, have potential severe infections and those who are more at risk of developing severe infections (e.g. immunocompromised) should be isolated. Handwashing/decontamination is the central and most essential part of ICP measures. It should be actively encouraged and regularly monitored to ensure adherence. The ward layout will influence how we manage ICP. This includes placement and number of alcohol dispensers, sinks, bathrooms, equipment storage and the number of cubicles. It is also worth reviewing ward cleaning policies to assess whether these can be streamlined, potentially freeing up beds/cubicles earlier and leading to cost improvement without putting patients and staff at risk. We encourage all our staff to be fully vaccinated (including seasonal influenza vaccines and MMR). Paediatricians need to be closely involved in antibiotic stewardship and act as role models for all aspects of infection control, particularly proper handwashing.